Habitat relationships of great gray owl prey in meadows of the Sierra Nevada Mountains - Ryan S. Kalinowski; Matthew D. Johnson; Adam C. Rich (Wildlife Society Bulletin)
ABSTRACT Annual productivity of great gray owls (Strix nebulosa) in California, USA, is thought to be largely dependent on vole (Microtus spp.) and pocket gopher (Thomomys spp.; hereafter, gopher) abundance, yet factors influencing these prey populations have not been thoroughly investigated. The abundance of voles and gophers has been influenced by vegetation and cattle grazing in other regions; and many meadows are grazed within the breeding range of great gray owls in the Sierra Nevada Mountains of California. We evaluated the influence of vegetation and cattle grazing on great gray owl foraging habitat by quantifying vole abundance, gopher abundance, and vegetation features in grazed and ungrazed meadows in 2010 and 2011. We found that vole presence was positively associated with sward height and corn lily (Veratrum californicum) dominance; vole abundance was weakly negatively associated with cattle grazing. Gopher abundance was negatively associated with site wetness, and weakly positively associated with stem density, the frequency of forb presence, cattle grazing, and the dominance of corn lily. To efficiently manage vegetation and cattle grazing to benefit great gray owl prey, we suggest prioritizing habitat for voles in wet meadows because gophers were not likely to be abundant in wet sites. Particularly in areas with moist soils, we recommend maintaining sward height commensurate with the habitat relationships of voles found in this study; >290 mm where corn lily is not dominant and 125 mm where it is. Sustaining sward height for voles should benefit great gray owls and other meadow or forest edge carnivores. © 2014 The Wildlife Society.